(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Dengue is an acute viral illness caused by an RNA virus and spread by aedes mosquito. These features may range to haemorrhage fever and shock. Oral manifestations are rare in dengue infections, in some cases may have oral features as the oral features as the only presenting manifestation. The dengue virus infections are usually self-limiting, dengue infection has come up as a public health challenges in the tropical and subtropical nations. This article provides information on dengue fever types, causes, symptoms, health screening programs, treatment, and epidemiology survey about dengue fever in India. As dengue fever is increasing in India, it is very essential to know more about this disease pattern, early detection of the virus and management will result in good recovery. Measures should be taken to control and prevent the disease spread. The physician should be aware about varied signs and symptoms of those conditions and ensure an early and adequate treatment plan. Future directions to combat this dreadful disease aim at method of mosquito control, development of vaccines and People should be aware of some seasonal diseases and prevention methods.